Lactobacillus delbrueckii subsp. bulgaricus 2038 and Streptococcus thermophilus 1131 ameliorate barrier dysfunction in human induced pluripotent stem cell-derived crypt-villus structural small intestine - Kobayashi, Kyosuke; Imai, Yuri; Shimizu, Yuka; Ogawa, Isamu; Nakai, Takaaki; Mizuno, Yuri; Kaneda, Yoshika; Watanabe-Yasuoka, Yumiko; Yamazaki, Fuka; Mochizuki, Junko; Sashihara, Toshihiro; Matsunaga, Tamihide; et al. (Frontiers in Immunology, 2025)
BackgroundLactic acid bacteria (LAB) have been widely used as probiotics which contribute to our health. We previously reported that Lactobacillus delbrueckii subsp. bulgaricus 2038 and Streptococcus thermophilus 1131, two yogurt starter strains, ameliorate the intestinal barrier dysfunction caused by tumor necrosis factor (TNF)-α and interferon (IFN)-γ in Caco-2 cells. However, Caco-2 cells differ from living organisms in various ways. We have developed a human induced pluripotent stem cell-derived crypt-villus structural small intestine (hiPSC-SI) was established with a villus-like structure containing constituent cells of the small intestine.MethodsA hiPSC-SI and LAB co-culture model was established to assess the impact of LAB on barrier function and elucidate the underlying mechanisms.ResultsThe medium on the luminal side for co-culturing cells and bacteria was examined and determined to use Hanks’ balanced salt solution without glucose in terms of bacterial survival rate. LAB were found to ameliorate permeability and decrease the gene expression of tight junction associated proteins induced by TNF-α and IFN-γ. Regarding cell differentiation, LAB suppressed the downregulation of LGR5, VIL1, LYZ and MUC2 by cytokines. Moreover, they ameliorated reduced mucin 2 protein production and decreased the number of mucin 2-positive cells. Finally, transcriptome analysis suggested that they ameliorated the aberration in cytokine-induced cell differentiation via an anti-inflammatory effect on intestinal stem cells.ConclusionsThe results indicate that LAB ameliorate the cytokine-induced dysfunction of intestinal barrier integrity and homeostasis disrupted by cytokines in a co-culture model of hiPSC-SI and LAB.